PENERAPAN KEGIATAN EKSTRAKURIKULER UNTUK MENGEMBANGKAN KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK AL- AZHAR 57 JAMBI - Rahma Virantika; Winda Sherly Utami; Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the implementation of traditional dance extracurricular activities in developing the kinesthetic intelligence of children aged 5–6 years at TK Al-Azhar 57 Jambi. The activities are designed to enhance children's abilities in various aspects of kinesthetic intelligence, including body coordination, balance, motor skills, strength and endurance, body flexibility, speed and agility, and tactile sensitivity. The data were obtained from primary sources through observation and interviews, as well as secondary data from documentation. The informant in this study was one traditional dance teacher at TK Al-Azhar 57 Jambi. The data analysis techniques used in this study included data reduction, data presentation, and data verification. The results showed that the implementation of traditional dance extracurricular activities at TK Al-Azhar 57 Jambi successfully supported the development of children's kinesthetic intelligence. These activities are conducted once a week, every Friday at 10:30 AM, for a duration of 30 minutes. The sessions are led directly by the dance teacher, and the children have shown progress in accordance with the indicators of kinesthetic intelligence.